Changes in the fatty acid pattern of plasma fractions of rats fed coconut, olive or sunflower oil. (Revista Española de Fisiología, 1995)
The fatty acid composition of plasma phospholipids, triacylglycerols and cholesteryl esters from rats fed diets supplemented (10% w/v) with coconut, olive or sunflower oil during six days has been studied. Rats fed the olive oil diet showed an increased amount of oleic acid whereas the animals fed the sunflower oil diet showed a higher content of linoleic acid than that of the other two groups. n-6 polyunsaturated fatty acids were mainly carried in phospholipid and cholesteryl-ester fractions. There were no differences in the amount of n-6 and n-3 polyunsaturated fatty acids. The effect of diet supplementation was shown after only six days of treatment and the results were similar to those reported in longer treatments.